PERUMUSAN STRATEGI PEMASARAN USAHA KECIL MENENGAH DENGAN PENDEKATAN SWOT ANALISIS UNTUK MENINGKATKAN PEMASARAN ( Study Kasus UD Ryan Colection ) - parjo, Su (JHP17 (Jurnal Hasil Penelitian), 2016)
Â The developing of SMEs can be big contribution for local development and poverty alleviation by decreasing unemployment people empowering. While theproblems in UD Riyaan Collection is how to mapping market segmentation andpositioning toward competitor, as well as how formulating precisely strategy toimproving sales marketing. By using developing strategy SWOT analysis thatcould be done by bag artisans of UD Riyaan Collection by utilizing Trainingand Expo that facilitated by the government, try to develop bag marketing areasoutside of Sidoarjo, sell bag product outside Sidoarjo, engage partnership withuniversities party, do market survey and following consumerâ€™s taste, search forand join relationship to potential suppliers, always try to improving productweakness and increase production efficiency and effectiveness. The joiningSWOT method with SPACE matrix resulting in aggressive method, method thatrun that are : follow the government programs related to SMEs development,such as : design training and human resource management, show exhibitionwith steps as follow: get cooperate with other institutions, get relationship withpotential market suppliers, apply effective and efficient work ways in order tocreate high productivity, and try to marketing product outside of Sidoarjo area. Keywords : Strategy, positioning, marketing, sales, weight.